Uncovering the constraints and difficulties faced by farmers engaged in Aloe vera cultivation in Haryana, India (Asian Journal of Agriculture, 2024)
Abstract. Mittal R. 2024. Uncovering the constraints and difficulties faced by farmers engaged in Aloe vera cultivation in Haryana, India. Asian J Agric 8: 88-94. The limitations of growing Aloe vera (L.) Burm.f. in Haryana, India are the focus of this study. During this, we look at the production, marketing, social, economic, technological, and infrastructure barriers to A. vera cultivation in Haryana. The researcher collected the farmers' data using a multi-purpose sampling technique to attain the study objectives. The five districts taken for the study include Haryana—Palwal, Nuh, Rewari, Jind, and Hisar. The study shows the challenges farmers face while growing A. vera. The most common constraints across all districts, according to key findings, are high marketing costs (78.67%), low farmer interest in A. vera cultivation (82%), the absence of a government policy setting a fixed price for medicinal plants (84%), higher input costs (79.33%), and insufficient seed or planting material (71.33%). Major challenges were also identified in the survey regarding poor transportation infrastructure (77.33%), overpowering irrigation water costs (77.33%), insufficient agriculture department oversight (77.33%), and a lack of technical awareness (79.3%). A lack of extension services on cultivation issues (65.33%), low product pricing (66%), limited processing units (68.67%), higher labor costs (69.33%), challenges to acquiring agricultural inputs (72%), and inadequate finance facilities (59.33%) are other major obstacles to success. Additional investigation discloses that there are major issues with market distance, inadequate local administration management, a lack of technically skilled workers, inadequate suggested manure dosages, shortages of labor, fear of theft, fear of stray animals, confined irrigation facilities, a poor understanding of post-harvest technology (72%), insufficient marketing channels (68.67%), and a lack of trained workers (67.33%). The outcomes underline the urgent need for focused interventions and legislative changes to address these multiple barriers. Enhancing market infrastructure, access to transportation, funding availability, technical education, and administrative management are essential strategies for raising crop production and sustainability in these geographic regions.
Keywords: Aloe vera, constraints, cultivation, farmers, medical plant